The embolisation of uterine arteries in treatment of uterine myomas - Kotarski, Jan; Bednarek, Wiesława (Menopause Review/Przegląd Menopauzalny, 2002)
Embolisation of arteries is widely used for treatment of haemorrhage due to advanced cases of cancers. It was also introduced for prevention and treatment of bleeding in obstetric pathology. Recently bilateral uterine embolisation was introduced for symptomatic myomas treatment. Preliminary data of 52 patients with symptomatic myomas who were treated with embolisation are presented. Techniques of the procedure and perioperative complications of six month observation are presented, also. MRI before procedure diminished the risk of embolisation of uterine arteries in cases of sarcoma. 3D-ultrasound was used for measurement of diameter and volume of myoma after surgery. Indication for such treatment were: contraindication for general or epidural anaesthesia, lack of agreement for blood transfusion (Jehova’s witnesses), lack of patient agreement for surgery. Limitation for procedure were: the size of tumor or pedunculous myoma.